Study on the Relationship Between Central and Local Finance --Based on the Perspective of Tax-sharing System - Liu, Xiuwei (IJRDO - Journal of Business Management, 2016)
the Tax-sharing reform as an important reform of China's financial filed, which has had a huge impact on the Central and Local fiscal revenue in China . This article first discusses the developments of the financial relationship between the Central and Local before and after the founding of China ,and then briefly reviews the content of tax-sharing system, and finally analyzes the effectiveness of tax-sharing system and the existing shortcomings.